Статичні електричні потенціали в біологічно активних зонах шкіри обличчя за умов формування емоційного вигорання в студентів - Тукаєв, Сергій; Федорчук, Світлана; Чікіна, Людмила; Герасько, Таїсія; Зима, Ігор; Зайченко, Олександр; Гаврилець, Юрій; Різун, Володимир; Богданов, Володимир; Горго, Юрій; Tukaiev, Sergii; Fedorchuk, Svitlana; et al. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Статичні електричні потенціали (СТЕП) у біологічно активних зонах шкіри (БАЗ) відображають рівень фонової активації мозкових структур і рівень психічного стресу. Мета дослідження – виявити зв’язки СТЕП у симетричних біологічно активних зонах шкіри обличчя з рівнем емоційного вигорання в студентів. Виявлена зворотна кореляція між формуванням емоційного вигорання й рівнем електричного потенціалу шкіри в правих білявушних БАЗ (r s = - .43, р < .05) відносно долоні як референтної ділянки. Знайдено кореляції між розвитком стадії опору вигоранню та фоновими СТЕП у правих і лівих лобних БАЗ (відповідно, r s = - .44 і r s = - .47, р < .05) і СТЕП у лівій лобній БАЗ після впливу негативних кадрів телевізійних новин (r s = - .50, р < .01). Це вказує на те, що формування емоційного вигорання знижує передпускову (до початку експерименту) емоційну напругу й відповідь, тобто силу реакції, на «зовнішні» негативні емоційні стимули. Отримані дані свідчать про те, що електродермальні потенціали можуть служити об’єктивними критеріями формування емоційного вигорання. Emotional burnout syndrome sees as a reaction to stress in interpersonal communication in the form of full or partial shutdown of emotions. V. Boyko dynamic model of burnout that was used as basis of this study classified in 3 stages in accordance with the mechanism of stress. There exist 3 phases: Anxiety Tension, Resistance, and Exhaustion. Strengthening of stressful factors in everyday life triggers the formation of emotional burnout (Anxiety Tension stage). The respondents with «Resistance» stage begin to economize emotion and characterize by emotional and moral disorientation. The central nervous activity reduction and the fall in energy tone are evident in the «Exhaustion» stage. Inadequate reactions to the different stimulus are associated with the hyperreactivity of the nervous system. The skin potential level (SPL) of facial biologically active zones (BAZs) reflects the level of background activation of brain structures and the level of mental stress. That is why skin potential level reflects the formation of emotional burnout. Purpose. The aim of the study was to detect the changes of SPL in symmetric biologically active zones of face skin (frontal, superciliary, paranasal, temporal, periotic and postaural) depending on the level of emotional burnout. Methods. 31 healthy volunteers (women and men) – first-third year students (Mage = 19.07, SD = 1.91 years, from 17 to 23 years) were recruited from the Taras Shevchenko National University of Kyiv, Educational and Scientific Centre «Institute of Biology and Medicine» and Faculty of Psychology, and participated for course credit during preexam period. Skin potential level was recorded via nonpolarizable silver electrodes from the symmetric biologically active zones of face skin (frontal, superciliary, paranasal, temporal, periotic and postaural) with the palm as a reference area. To determine the stages of burnout we used the Boyko «Syndrome of emotional burnout» test adapted for students by Tukaiev and Vasheka. The value of each of Burnout stages was measured on a scale from 0 to 120 points: 0 to 36 points – the stage was not formed, 37 to 60 points – the stage was under development, 61 to 120 points – the stage was formed. The Speerman rank test was carried out for the correlation analysis. Results. Inverse correlation was found between the formation of emotional burnout and the skin potential level in right periotic BAZ (parotid BAZ) (r = - .43, p < .05). We found correlation between the development of the Resistance stage of burnout and background SPL in the right and left frontal BAZ (respectively r = - .44 and r = - .47, p < .05) and SPL in the left frontal BAZ after the exposure of negative frames of documentaries (r = - .50, p < .01). Conclusion. Our data indicates that the formation of burnout reduced the prestarting initial emotional tension and response strength to «external» negative emotional stimuli. It indicates that electrodermal potentials can serve as objective criteria of formation of emotional burnout.
The Skin Potential Level of Facial Biologically Active Zones as Indicators of the Level of Emotional Burnout in Students.
Keywords: статичні електричні потенціали (СТЕП); рівень емоційного вигорання; біологічно активні зони шкіри людини (БАЗ); skin potential level (SPL); emotional burnout; biologically active zones (BAZs)